THE FRAMEWORK OF LOCAL TOURISM DEVELOPMENT GOVERNANCE BASED ON AGILE GOVERNANCE: A STUDY IN DAYUN DISTRICT, SIAK REGENCY - M. Rafi; Rico Purnawandi Pane; Ali Yusri; Wan Asrida; Ardiansyah Ardiansyah; Meris Essio Mento (Jurnal Administrasi Publik, 2025)
This study aims to explain the existing condition of tourism governance and recommendations for strengthening local tourism development governance based on agile governance in the Dayun Sub-District, Siak Regency, Riau Province. The urgency of strengthening local tourism development governance based on agile governance is emphasized by the potential tourist attractions with various types of natural, artificial, historical, cultural and culinary tourism. Through a qualitative approach, utilizing focus group discussion (FGD) data and literature reviews, this study highlights the critical role of each actor in the tourism sector in strengthening local tourism governance based on agile governance. The research findings emphasize that tourism destination development should aim to show strategic paths and recommendations that must be followed by all stakeholders based on an agile and sustainable paradigm. This study underlines the importance of recommendations for strengthening tourism governance based on agile governance, where every organization and actor in the tourism sector must adopt adaptive governance to face rapid change and uncertainty in the future. This study contributes to understanding the local government governance framework related to efforts to strengthen governance that can act as a stimulus for sustainable tourism growth.